Effect of Using Two Music Types on Non-Pregnant Non-Lactating Arabi Ewes Behaviour As a Tool for Welfare Improvement - Meshabaz, Ronak A.; Hussein, Nizar J.; Mersham, Mhamed A.M.; Mhamed, Mhamed S.S. (Science Journal of University of Zakho, 2017)
The present study was designed to determine whether playing two music types will improve the behaviour of non-pregnant, non-lactating Arabi sheep. Thirty Arabi ewes, aged 2 – 3 years, were included in the study. Ewes were divided into three groups, 10 ewes each. The groups were: Control (with no music exposure); Classic music exposure and Fast music exposure. The sound level for classic and fast music groups was 80 dB with the frequency of 1 KHz. The behavioural data were collected using direct observations for six respective days. Results revealed that using music, both classic and fast, significantly decreased the frequency of aggressive behaviours (P < 0.001), vocalization (P < 0.01), defecation (P < 0.05) and walking behaviour (P < 0.05). In addition, there were significant effects of music on the average time spent standing (P < 0.01), lying and feeding (P < 0.001). Whereas no significant difference was found in the average time spent drinking. It was shown that there were significant differences in time spent lying (P < 0.01) and time spent feeding (P < 0.01) over time. Finally, there was a significant difference in the proportion of time spent lying (P < 0.001) as well as in the proportion of time spent feeding between control and music groups (P < 0.01). From this study, it can be concluded that exposing non-pregnant, non-lactating ewes to classical music is beneficial for ewes’ welfare, due to the reduction of aggressive behaviour.